Ultrasound-assisted extraction, purification, sulfation of Perilla leaves polysaccharide and hypoglycemic and hypolipidemic activities - Jing Guan; Peng Guo; Meng Chen; Wenzhao Wang; Xinyu Chen; Qiuyun Li; Yiyang He; Jiayue Liang; Ningxin Yu; Pengna Gao; Yanli Wu (Ultrasonics Sonochemistry)
Perilla leaves are a common traditional medicinal and edible crop, in order to further explore its medicinal value, after determining the optimal ultrasound-assisted extraction conditions a neutral polysaccharide was extracted. Its structure was analyzed, and sulfation modification was carried out. After purification by different column chromatography, the optimal process for sulfation modification of PLP-2-1 was established, and sulfated modified PLP-2-1 (S-PLP-2-1) was successfully prepared. The potential structural framework and molecular weight of PLP-2-1 were determined by high performance liquid chromatography (HPLC), methylation analysis, and nuclear magnetic resonance (NMR) techniques, while sulfated modified S-PLP-2-1 maintained a high degree of structural similarity to PLP-2-1. Particle size analysis, Zeta potential measurement, infrared spectroscopy, and NMR analysis confirmed the presence of sulfate groups in S-PLP-2-1, while thermogravimetric and rheological analyses provided support for the development and utilization of these two polysaccharides. After determined the safe concentration range in vitro, the antioxidant and hypoglycemic activities of PLP-2-1 and S-PLP-2-1 were measured. Besides, the effects on the levels of total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) in oleic acid (OA) induced high-fat HepG2 cells of both polysaccharides were determined. The results indicated that the various biological activities of S-PLP-2-1 were significantly enhanced after sulfation modification. Therefore, PLP-2-1 and S-PLP-2-1 have the potential to be developed as drugs for anti-glycolipid metabolism disorders.